2016
DOI: 10.2119/molmed.2016.00225
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis induces Telomere Shortening: a Potential Mechanism Responsible for Delayed Pathophysiological Events in Sepsis Survivors?

Abstract: Sepsis survivors suffer from additional morbidities, including higher disk of readmissions, nervous system disturbances and cognitive dysfunction, and increased mortality, even several years after the initial episode of sepsis. In many ways, the phenotype of sepsis survivors resembles the phenotype associated with accelerated aging. Since telomere shortening is a hallmark of aging, we investigated whether sepsis also leads to telomere shortening. Male balb/c mice were divided into two groups: the control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…In contrast, we found decreased telomere length in CD4+ T cells but not CD8+ T cells of septic patients, despite upregulated telomerase and moreover despite upregulated shelterin complexes, which protect telomeres from shortening. Similarly to our study, decreased telomere length was also observed in a mouse model of sepsis and in human peripheral blood cells of septic patients, which was explained as possibly resulting from oxidative stress or the release of several inflammatory factors [38]. In this case, increased telomerase activity cannot compensate for these mechanisms.…”
Section: Discussionsupporting
confidence: 84%
“…In contrast, we found decreased telomere length in CD4+ T cells but not CD8+ T cells of septic patients, despite upregulated telomerase and moreover despite upregulated shelterin complexes, which protect telomeres from shortening. Similarly to our study, decreased telomere length was also observed in a mouse model of sepsis and in human peripheral blood cells of septic patients, which was explained as possibly resulting from oxidative stress or the release of several inflammatory factors [38]. In this case, increased telomerase activity cannot compensate for these mechanisms.…”
Section: Discussionsupporting
confidence: 84%
“…Findings from a recent small study of septic patients ( n = 9) showed that significant reductions in telomere length may also occur over short time periods, namely over one week [20]. However, the correlation between changes of leukocyte telomere length in this acute setting of critically ill, metabolically stressed patients and outcome has not been evaluated to date.…”
Section: Introductionmentioning
confidence: 99%
“…In the long term, these plausible DNA mutations and deletions can significantly impact patient quality of life and predispose the survivors of inflammatory catastrophes to several morbid consequences. In this regard, a recent publication from our group showed that sepsis induces telomere shortening ( 55 ), confirming that inflammation affects telomere length ( 56 ) and that stress-induced premature senescence is a telomere-dependent process ( 57 ). Despite that, however, the other evidence in the literature addressing this topic is controversial and/or indirect.…”
Section: Introductionmentioning
confidence: 55%